A Mathematical Model of Diet Menu Problem Based on Boolean Linear Programming Approach - Harahap, Latifah Hanum; Nasution, Mahyuddin K. M.; Sawaluddin, Sawaluddin (Sinkron : jurnal dan penelitian teknik informatika, 2023)
This study aims to model the diet menu problem based on a Boolean Linear Programming approach. A balanced diet is the key to a healthy lifestyle. A balanced diet is a diet that combines foodstuffs in the right amount of food components in one menu (dishes using certain recipes). When you have an unbalanced diet, your body will not get the right amount of nutrients. This is what causes the importance of managing the diet menu. Because of that, a diet menu problem model was formed based on the Boolean Linear Programming approach to cover a varied range of daily diet menu management and meet daily nutritional needs while minimizing costs. The stages of establishing the diet menu problem model are carried out by determining the notations, parameters, variables, objective functions, and some constraints related to the diet menu.